2021
DOI: 10.1590/2358-2936e2021021
|View full text |Cite
|
Sign up to set email alerts
|

Spawning season, recruitment, and growth of the freshwater prawn Macrobrachium lamarrei (H. Milne-Edwards, 1837) in a perennial wetland, northeastern Bangladesh

Abstract: Spawning season, recruitment, and growth of the freshwater prawn Macrobrachium lamarrei were studied in a perennial wetland, northeastern Bangladesh during October 2016 to September 2017. Spawning season was estimated based on the monthly variations of percent ovigerous females. Recruitment and growth were estimated using the time series of the lengthfrequency distributions. We compared the von Bertalanffy growth function (VBGF) and the Pauly and Gaschütz growth function (PGGF) to identify any seasonal oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In fact, this was not possible in this case, as the present study was based on fishery-dependent data. However, relatively high temperatures (23-33 • C) throughout the year at our study site may cause year-round spawning of this species, as reported by several studies [38,[71][72][73][74][75][76][77][78][79][80]. The spawning seasons of some gobiid species are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In fact, this was not possible in this case, as the present study was based on fishery-dependent data. However, relatively high temperatures (23-33 • C) throughout the year at our study site may cause year-round spawning of this species, as reported by several studies [38,[71][72][73][74][75][76][77][78][79][80]. The spawning seasons of some gobiid species are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 62%
“…The GSI showed that G. giuris could release eggs throughout the year with three peaks: two minor peaks in January-February and April-May, and a major peak occurring in August-November. The most vital environmental factors directly or indirectly influencing the reproduction of aquatic animals are temperature, rainfall, and photoperiod [68][69][70][71][72][73]. The seasonality of these factors also influences biological cycles by ensuring larval occurrence during the periods of available food [73,74].…”
Section: Discussionmentioning
confidence: 99%